Manifestation of the Female Character in Mohammad Hijazi Works: An Individual and Social Approach - Manijeh Salehpanah; Heidar Hasanlo; Mehri Talkhabi (Iranian Evolutionary Educational Psychology Journal)
Objective: The exploration of the woman and her societal status holds great significance within the realm of contemporary literature, serving as a focal point for numerous authors. One such writer, Mohammad Hijazi, has emerged as a prominent figure in the post-constitutional era, crafting invaluable literary pieces that revolve around women and the intricate issues they face amidst the tumultuous circumstances prevailing in society. Through his works, Hijazi effectively sheds light on the social standing of women during those particular times. Methods: By means of a descriptive-analytical study that heavily relies on resources found within libraries, researchers have meticulously examined the societal position of women, exploring both the physical and psychological aspects, all within the context of Hijazi's noteworthy works. Results: It is worth noting that, despite their gender, women possess a considerable amount of influence when it comes to the appointment and allocation of administrative as well as judicial roles within their respective societies. Conclusions: In conclusion, Mohammad Hijazi's literary works provide a nuanced portrayal of the female character by highlighting the significant individual and societal roles women play, emphasizing their influence in administrative and judicial domains despite prevailing societal challenges.